Pendidikan sebagai Barang atau Jasa Publik dan Swasta - Syukron, Muhammad; Zahruddin, Zahruddin (Lembaga Yasin AlSys, 2022)
In Indonesia, education is no longer purely a public good because some of it has been privatized by the government, so that people can no longer get it for free. It can be seen from the large number of private schools not only from local origins, but many international schools have been established in Indonesia, and also occur in various countries. This type of research is qualitative research using documentation study data collection methods in the form of relevant books and journals. Data analysis techniques start from data collection, data reduction, presentation and discussion of data then conclusions are drawn. The result of this research is that education can be a public good and can be a private good. Education as a public good because its provision is free, universal and equal access is the basis for producing other public goods. Education as a private good because of a necessity there is competition in getting a decent education. The competition must be purely a competition of intelligence and intellect, not a competition for money or position.